2011
DOI: 10.3329/bmrcb.v37i3.6196
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of homocysteine in preeclamptic women

Abstract: It has been hypothesized that maternal hyperhomocysteinemia to be associated with preeclampsia. The aims of the present study were to examine maternal serum levels of total homocysteine in preeclamptic women and its association with the severity of the disease. The study population consisted of 30 preeclamptic patients and 30 matched healthy pregnant women. Serum levels of total homocysteine were assessed using enzyme immunoassay method. Maternal serum levels of total homocysteine were significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…Premlata et al showed the mean levels of severe PE and mild PE 15.9±6.3 vs 12.3±4.2 (p value =0.01). 4 Several other studies were in consonance with the her results such as Khosrowbeygi A et al and Makedos G et al 6,10 Based on the findings of present study it can be concluded that maternal serum homocysteine seems to have a causal role in pathogenesis of pre-eclampsia, however measurement of homocysteine concentration did not determine the severity of pre-eclampsia. In present study the pre-eclamptic group had higher incidence of caesarean sections (56.66%).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Premlata et al showed the mean levels of severe PE and mild PE 15.9±6.3 vs 12.3±4.2 (p value =0.01). 4 Several other studies were in consonance with the her results such as Khosrowbeygi A et al and Makedos G et al 6,10 Based on the findings of present study it can be concluded that maternal serum homocysteine seems to have a causal role in pathogenesis of pre-eclampsia, however measurement of homocysteine concentration did not determine the severity of pre-eclampsia. In present study the pre-eclamptic group had higher incidence of caesarean sections (56.66%).…”
Section: Discussionsupporting
confidence: 68%
“…7 Several other studies were in consonance with the present study. 5,6,[8][9][10] On the contrary Zeeman GG et al did not agree with our observations and there was no significant difference in maternal serum levels of homocysteine between pre-eclampsia and normal pregnancy (5.1±1.7 μmol/l vs 4.7±1.3 μmol/l p value =0.56) and they stated that serum homocysteine levels were not helpful in the prediction of PE. 11 Hietala R et al also stated that there was no difference between pre-eclampsia and normotensive women (6.42, 7.55μmol/l vs 6.45, 7.34 μmol/l).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Leeda et al (24) performed methionine loading tests on women with intrauterine growth retardation post-partum and found that 19.2% had hyperhomocysteinemia. It has been demonstrated that homocysteine levels are higher in preeclamptic women than those in normal pregnants (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…6 In a similar study done by Khosrowbeygi A and Ahmadvand H and Laskowska M et al maternal serum levels of total homocysteine were significantly higher in preeclamptic than in normal pregnant women. 7,8 Some studies suggested that infection and inflammatory processes are related to preeclampsia. The role of inflammation and infection in the pathogenesis of preeclampsia is significant in developing countries, where the high incidence of chronic subclinical infection may contribute to the high incidence of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%